Avaliação do trabalho docente e suas especificidades na UNESP - Biffi, Evandro José (Universidade Federal de São Carlos, 2018)
Our objective in this research was to analyze the assessment procedures and instruments of the teaching work, as well as the education quality and assessment conception, by the teachers and the institution. We began with the hypothesis that the assessment would have a quantitative characteristic, whose tendency would be measuring the productivity. As a start, we analyzed institutional documents, such as: institutional assessment reports; statistical yearbooks; assessment instruments; documents from the Assessment Forum; resolutions; ordinances; letters; instructions; related legislation; and also journals and publications of the servers and teachers union. We could obtain data about the university, its distinct expansion cycles, teaching work and assessment processes to which it is submitted. In a second part of the research, we conducted eight semi-structured interviews with teachers with different profiles. The reports expressed important nuances about the work conditions and views about the assessment processes and the education quality. There were both contradiction as convergences among the conceptions of assessment and quality of the institution and those supported by the teachers. The teacher views about the effects of the assessment system vary according to the profiles and different positioning toward the current policies and the practices in the university. We noticed some specificities in the teaching work assessment at UNESP and its instruments. These, built in the historical context of the State Reform and subordinated to the managerialist ideology and to the productivity and efficiency indexes, assume prominence. The instrumental rationality connects to the effort of the consolidation of the research and the post-graduation. What implied in the hyper-bureaucratization, expressed in hyper-normativity in the performance punctuation. We verified an infinity of resolutions, commission and management structures of teaching work control and its production. The hyper-normativity implies work intensification and results in obstacles to the education quality. The quantophrenia and the instrumental rationality start become part of the university routine, awakening the accession of many who believe in the possibility of measuring the quality of the education, and tend to naturalize the academic productivism and the quantitative assessment of the performance. Yet, also awakened criticism and questionings. Although there was a trend of naturalization of the academic productivism and the assessment processes, most of the teachers pointed to impasses, if not obstacles, to the realization of the education quality.
Keywords: Políticas educacionais; Avaliação; Intensificação do trabalho; Produtivismo acadêmico; Qualidade da educação; Education policies; Assessment; Work intensification; Academic productivism; Education quality; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO